Prospects for legislative support in the field of guardianship and care of adults in Ukraine - Sotska, Alla (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
In the article, the author noted a wide range of normative legal acts, which contain norms and provisions regulating legal relations in the field of guardianship and care of adult incapacitated persons and persons whose legal capacity is limited. At the same time, it has been criticized due to the presence of gaps, inconsistencies and contradictions, which in turn significantly negatively affects the practice of implementing the relevant legislation and, as a result, the quality of life of the specified categories of persons and the level of security of their rights, legitimate interests and needs. The lack of statistical data on the direction of research is noted, which significantly complicates the analysis of the situation in the direction under study. In addition, in the opinion of the author, the priority directions of state policy regarding the improvement of legislative regulation of the sphere of guardianship and care of adults are highlighted, which include the need for: in-depth study of the problems of incapacitated persons and persons whose legal capacity is limited; research of the best international experience in this field and consideration of the possibility of its implementation in national practice; creation of the necessary legal framework; ensuring the formation of public awareness regarding the positive perception of the specified categories of the population. The importance of the draft Law of Ukraine «Basics of the legislation of Ukraine on the guardianship and care of adult incapacitated persons and persons whose legal capacity is limited, their social protection» developed and submitted to the Verkhovna Rada of Ukraine at the time was noted, and the Government's decision to withdraw this draft law, which was destructive for the field under study, was noted. Finally, a list of issues in the field of guardianship and care of adults that need urgent solutions is given, in particular, regarding the formation of a conceptual apparatus; determination of the principles of guardianship and care over such persons and subjects of administration in this area; determination of legal statuses of guardianship and guardianship bodies, incapacitated persons and persons whose legal capacity is limited, guardians and custodians; regulation of the procedure for keeping records of adult persons who are under guardianship and care, as well as the issue of ensuring their property rights, etc.